Nigerian Military, Guerrilla Warfare and Cost of Fighting Terrorism: An Assessment of the Fight against North-East Insurgency 2012-2019 - Tahir, Lawan Jafaru; Umar, Ombuguhim Salman (NIU Journal of Humanities; Vol 7 No 1 (2022): NIU Journal of Humanities, Vol. 7 No. 1, March 2022DO - 10.58709/niujhu.v7i1.1401, 2022)
This paper discusses the general performance of the Nigerian military in their war against the insurgency in north-eastern Nigeria. Apart from the methodology applied which was both primary and secondary source, background of the Nigerian military was discussed as to their participation in the previous operations. The central argument here is how fighting guerilla war has become so difficult for them because of either the first experience or lack of technical know-how to approach it. The fighting took Nigerian Soldiers more than one decade as such this research discovered some of the problems associated to this prolong and devastated war. Among them include the problem of corruption which the military institution is being accused. Funds meant for the operation were diverted and several examples of this have been revealed in the paper. General operation of the war and the assessment of Nigerian soldiersâ€™ performance are critically examined. In this regard, the counter-insurgency was faced with serious resistance from the insurgents who appeared very top to the Nigerian security. In this work, some war techniques that were demonstrated by the Boko Haram militants have beensubstantiated which were entirely new to the knowledge of the Nigerian military. The research at the end discusses way out to handle such problems in future by suggesting the total review of the military institution in terms of training, operation, discipline, professionalism, improvement in  intelligence gathering and possession of modern warfare technology. Keynotes: Military, Operation, War, Terrorism, Insurgency, Boko Haram